PENDIDIKAN KARAKTER DALAM PERSPEKTIF SUNNAH SEBAGAI UPAYA PENINGKATAN MUTU BINA PRIBADI ISLAMI PADA PESERTA DIDIK DI SDIT IBNU MAJAH - Luqman Hakim; Yuli Habibatul Imamah; Ali Masyhar (UNISAN JURNAL, 2023)
The purpose of character or moral education is to overcome the moral decline that occurs in the current generation. The methodology in this study was qualitative research in the form of field research which was strengthened by literature and field studies. Literature study has five types of contents of research notes used in data processing, namely extracts, summaries, descriptive notes, and reflective notes. While the field study in this researcher conducted data collection by means of observation, interviews and documentation. This research was held because moral problems are a problem that must be a common concern. Morals or character can be grown and shaped by education. Character education is one solution to this problem. Character education takes concepts from the Qur'an, the sunnah of the Prophet and the government's concept to support the character education strengthening program (PPK) that has been launched by the government. The conclusion in this study is that character education can be integrated into learning in schools in all subjects, especially Islamic Religious Education as a subject that plays a major role in instilling religious values ​​in students. Character education is used as an effort to improve the quality of implementing Islamic Personal Development activities for students at SDIT Ibnu Majah Jatimulya South Tambun Bekasi Regency